Eksplorasi Pembentukan Teacher Identity melalui Pengalaman Hidup - Puspitaningtyas, Ellen (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This research aims to explore construction of teacher identity throughlife experiences. Data were collected from observation, interviews, and document analysis. The results of this researchindicate that in the perspective of discourse identity, TN is a teacher who emphasizes contextual learning and student centered learning. Based on the perspective of nature identity,kinesthetic learning and her fondness in mathematics have a major influence on her interest in physics. Meanwhile, from the perspective of affinity identity, family and role models greatly influence TN's beliefs about learning and her decision to have a career as a teacher. From the perspective of institution identity,formal institutions have both positive and negative impact on the construction of TN’s identity, while informal institutions such as organizations have a major influence on TN’s physics interests and rhetorical skills.